2022
DOI: 10.3389/falgy.2022.809646
|View full text |Cite
|
Sign up to set email alerts
|

Navigating patients with atopic dermatitis or chronic spontaneous urticaria during the COVID-19 pandemic

Abstract: A rapid spread of different strains of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to an unprecedented pandemic. Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, the medical body has encountered major obstacles concerning disease management at different levels. Even though patients infected with this virus mainly present with respiratory symptoms, it has been associated with a plethora of well-documented cutaneous manifestations in the literature. However, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Dermatologists should be aware of these reactions to be able to provide proper patient education and shed light on appropriate management during the COVID‐19 pandemic. A recent review on COVID‐19 in patients with atopic dermatitis and chronic spontaneous urticaria revealed that flare‐ups are common 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatologists should be aware of these reactions to be able to provide proper patient education and shed light on appropriate management during the COVID‐19 pandemic. A recent review on COVID‐19 in patients with atopic dermatitis and chronic spontaneous urticaria revealed that flare‐ups are common 36 …”
Section: Discussionmentioning
confidence: 99%
“…A recent review on COVID-19 in patients with atopic dermatitis and chronic spontaneous urticaria revealed that flare-ups are common. 36 The advent of COVID-19 vaccines offered a glimpse of hope to fight the pandemic. However, there have been numerous reports of ACRs post-vaccine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Further confirmation of the antiviral potential of photochemotherapy comes from the finding of photoinactivation potential in plasma with Amotosalen and 3 J/cm 2 of UVA light of six RNA-enveloped viruses, including SARS CoV [ 57 ]. Beyond the newly explored therapeutic potential, the promising role of phototherapy is also related to its choice as a viable therapeutic alternative to immunomodulating/immunosuppressive drugs used in AD and similar conditions whose use should be limited because of their ability to impact vaccine-induced immune responses [ 58 , 59 , 60 , 61 ] and for their suppressive action on intrinsic antiviral immunity [ 62 , 63 , 64 ] except for dupilumab, whose evidence of use in the pandemic era is reassuring [ 65 , 66 , 67 ].…”
Section: Atopic Dermatitis Treatmentmentioning
confidence: 99%
“…It affects approximately 10% of the population [ 127 ]. Most often, atopic dermatitis occurs in early childhood, also in infancy, and manifests itself as a rash with redness and dryness of the skin, as well as severe itching [ 128 , 129 ]. Patients tend to scratch skin lesions, which leads to numerous bacterial superinfections and exacerbates the lesions, causing discomfort and negatively affecting the patients’ quality of life [ 127 ].…”
Section: Introductionmentioning
confidence: 99%